The Role of Village Fund in Local Economic Development through Revamping the Bah Biak Waterfall Ecotourism Area - Saragih, Jef Rudiantho; Asaad, Mhd.; Nurhayati, Nurhayati (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2024)
The Village Fund (VF) drives local economic growth by fostering ecotourism development. This study investigates the impact of the VF program on Local Economic Development (LED) in the Bah Biak Waterfall Ecotourism area, located in Sidamanik Sub-district, Simalungun Regency, North Sumatra. The VF program aims to enhance community income, create employment opportunities, and improve the productive capacity of rural communities. We use a purposive sampling method to collect data from 64 households out of 174 in the area. Critical indicators of LED, including local employment, household income, and expenditure, were analyzed using paired sample t-tests to compare conditions before and after using the VF. The results indicate a significant increase in local employment, household income, and expenditure following the utilization of the VF. This research underscores the importance of community participation in all stages of program activities, from planning to evaluation, and highlights the need for enhanced involvement in monitoring processes. The findings contribute to understanding how the VF can effectively support local economic development and provide recommendations for future ecotourism package development that integrates local resources and attractions. Future studies will focus on developing integrated ecotourism packages that combine multiple attractions and activities in the region, such as the panorama of tea plantations, Arabica coffee farming, creative economics based on beekeeping, and educational tourism related to sustainable practices.